Inorganic functional powder material with porous microsphere structure and preparation method thereof

CN116492942BActive Publication Date: 2026-10-13INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210058325.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-19
Publication Date
2026-10-13
Estimated Expiration
2042-01-19

AI Technical Summary

Technical Problem

当前工艺方法制备得到的碱式磷酸钙多为片状的不规则晶体,当其作为色谱柱的填充材料时,容易发生破碎,在使用过程中受到一定限制

Benefits of technology

[0062](1)本发明提供的具有多孔微球结构的无机功能粉体材料的制备方法可以调控无机功能粉体材料的比表面积和抗压强度,在保证较大比表面积的同时使抗压强度更高,并且孔径和粒径可以调控,以粒径为50nm的棒状碱式磷酸钙为例,在较优条件下,所得无机功能粉体材料的抗压强度≥7.4MPa,比表面积≥58.3m2/g,孔体积≥0.47cm3/g,平均孔径≥35.6nm,中值粒径≥17.5μm;以粒径为100nm的针状碱式磷酸钙为例,所得无机功能粉体材料的抗压强度≥10.6MPa,比表面积≥80.2m2/g,孔体积≥0.49cm3/g,平均孔径≥46.4nm,中值粒径≥11.2μm;粒径为140nm的柱状氟磷酸钙为例,所得无机功能粉体材料的抗压强度≥12.1MPa,比表面积≥24.16m2/g,孔体积≥0.16cm3/g,平均孔径≥12.4nm,中值粒径≥94.2μm。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116492942B_ABST
    Figure CN116492942B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of inorganic functional powder materials with porous microspheres structure and its preparation method, the preparation method includes the following steps: (1) mixing inorganic particle, dispersing agent and binder, then sequentially ultrasonic and dispersion, obtain suspension;(2) the suspension of step (1) obtained is carried out condensation treatment, then sequentially spray drying and calcination, obtain the inorganic functional powder material.The inorganic functional powder material is obtained by the preparation method.The inorganic functional powder material with porous microspheres structure provided by the present application has large specific surface area, rich pore, uniform particle size and pore size distribution, high compressive strength, and can be used in coating filler, bone filling material, protein separation medium and drug sustained-release carrier and other fields.The preparation method of the inorganic functional powder material with porous microspheres structure provided by the present application is simple to operate, and can be popularized in industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic materials, specifically to an inorganic functional powder material with a porous microsphere structure and its preparation method. Background Technology

[0002] Inorganic functional powders have wide applications in pharmaceuticals, dyes, pigments, fillers, and information recording. In the fields of chemical engineering and new materials, porous microspheres made from powders occupy an important position.

[0003] Inorganic powder materials synthesized by general chemical methods have various shapes and no pores. Among them, plate-shaped, needle-shaped, or flaky inorganic powder materials are prone to breakage when used as fillers, which limits the application range of inorganic powder materials.

[0004] The main methods for preparing porous microsphere-structured inorganic powder materials include chemical foaming, pore-forming agent methods, organic impregnation methods, and emulsion methods. Inorganic powder materials prepared by chemical foaming generally have pore sizes above the micrometer level, and most are closed pores with poor pore penetration, making it difficult to control pore size and volume. Inorganic powder materials prepared by pore-forming agent methods have low porosity and a wide pore size distribution. Inorganic powder materials prepared by organic impregnation methods are prone to developing microcracks and have relatively poor compressive strength. Emulsion methods can adjust the morphology of the product by adjusting the concentration of each component, but the cost is high and it is difficult to scale up production.

[0005] Taking basic calcium phosphate as an example, it possesses excellent biocompatibility, bioactivity, and ion exchange properties, and is often used as a coating packing material, bone filler, protein separation medium, and drug sustained-release carrier. However, the basic calcium phosphate prepared by current processes is mostly in the form of irregular, flaky crystals. When used as a packing material for chromatographic columns, it is prone to breakage, which limits its application.

[0006] CN105056298A discloses a method for preparing porous calcium phosphate microspheres with large surface pores. The method involves mixing a polysaccharide gel solution and a thickener solution, followed by sequential ultrasonication, freezing, and vacuum drying to obtain porous calcium phosphate microspheres. These porous calcium phosphate materials are millimeter-sized materials with large particle sizes and small specific surface areas, making them unsuitable for drug carriers.

[0007] CN104548213A discloses a porous spherical calcium phosphate bone filler material and its preparation method. The method involves solidifying, washing, and drying calcium phosphate powder to obtain microspheres, which are then calcined to obtain the porous spherical calcium phosphate bone filler material. However, the calcium phosphate material obtained by this method has poor compressive strength and is easily broken, thus limiting its application range.

[0008] Therefore, how to control the morphology and structure of inorganic powders and avoid the shortcomings of traditional processes, such as wide particle size distribution, small specific surface area and poor compressive strength, is a problem that needs to be solved. Summary of the Invention

[0009] To address the above problems, the present invention aims to provide an inorganic functional powder material with a porous microsphere structure and its preparation method. Compared with the prior art, the inorganic functional powder material provided by the present invention has a large specific surface area, adjustable particle size, and high compressive strength. The preparation method of the inorganic functional powder material provided by the present invention is simple to operate and can be industrially promoted.

[0010] To achieve this objective, the present invention adopts the following technical solution:

[0011] In a first aspect, the present invention provides a method for preparing an inorganic functional powder material having a porous microsphere structure, the preparation method comprising the following steps:

[0012] (1) Mix inorganic particles, dispersant and binder to obtain a suspension;

[0013] (2) The suspension obtained in step (1) is subjected to condensation treatment, and then spray drying and calcination are performed in sequence to obtain the inorganic functional powder material.

[0014] In this invention, by mixing inorganic particles with dispersants and binders, the inorganic particles can be fully dispersed, reducing particle agglomeration and forming a uniform suspension. Simultaneously, the addition of the binder imparts viscosity and adhesive properties to the suspension. The suspension, after condensation treatment, is spray-dried to form spherical droplets, and the binder rapidly loses water, binding the inorganic particles into spherical particles. This is then calcined to obtain an inorganic functional powder material with a porous microsphere structure. In this invention, the binder binds the inorganic particles together, resulting in abundant and uniform pores. The condensation treatment reduces crystallization during spray drying, giving the inorganic functional powder material a large specific surface area and pore size. The curing of the binder and calcination conditions significantly improve the compressive strength of the inorganic functional powder. In contrast, existing methods for preparing porous microspheres use pore-forming agents or evaporated organic solvents to form pores, resulting in a wide pore size distribution and poor compressive strength. Porous microspheres prepared by chemical foaming methods often have closed pores, and inorganic powder materials synthesized directly by chemical methods generally lack pores. The preparation method provided by this invention has a uniform pore size distribution, a large specific surface area, and high compressive strength. Furthermore, the particle size and pore size of the inorganic functional powder material can be controlled.

[0015] Preferably, the dispersant in step (1) is first mixed with the solvent, and then mixed with the inorganic particles and the binder.

[0016] Preferably, the solvent includes any one or a combination of at least two of the following: purified water, distilled water, deionized water, or ultrapure water.

[0017] Preferably, the dispersant comprises any one or a combination of at least two of sodium polyacrylate, sodium polycarboxylate, sodium dodecylbenzenesulfonate, sodium citrate, sodium metaphosphate, or sodium pyrophosphate, wherein typical but non-limiting combinations include combinations of sodium polyacrylate and sodium dodecylbenzenesulfonate, combinations of sodium dodecylbenzenesulfonate and sodium citrate, or combinations of sodium citrate and sodium metaphosphate, etc.

[0018] Preferably, the mass percentage of the dispersant in the suspension is 0.1%-2.5%, for example, it can be 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2% or 2.5%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0019] The present invention preferably controls the mass percentage content of the dispersant within a specific range, which can make the suspension more uniform and stable, which is beneficial for spray drying to obtain particles with a narrower particle size distribution, and at the same time can make the spherical structure of the particles more regular.

[0020] Preferably, the inorganic particles include inorganic metal oxides and / or inorganic salts.

[0021] Preferably, the inorganic particles include any one or a combination of at least two of aluminum oxide, magnesium oxide, silicon oxide, zirconium oxide, aluminum silicate, basic calcium phosphate, or calcium fluorophosphate, wherein typical but non-limiting combinations include combinations of aluminum oxide and magnesium oxide, combinations of silicon oxide and zirconium oxide, or combinations of aluminum silicate and basic calcium phosphate, etc.

[0022] Preferably, the inorganic particles in the suspension have a mass percentage content of 10%-50%, for example, it can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, or 50%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0023] Preferably, the particle size of the inorganic particles is 1nm-20μm, for example, it can be 1nm, 2nm, 4nm, 6nm, 8nm, 10nm, 100nm, 200nm, 400nm, 450nm, 500nm, 1μm, 2μm, 5μm, 8μm, 12μm, 15μm, 18μm or 20μm, preferably 40nm-500nm.

[0024] Preferably, the morphology of the inorganic particles is any one or a combination of at least two of the following: rod-shaped, needle-shaped, plate-shaped, spherical, ellipsoidal, columnar, or plate-shaped. Typical but non-limiting combinations include combinations of rod-shaped and needle-shaped, plate-shaped and spherical, or columnar and plate-shaped, etc.

[0025] Preferably, the adhesive comprises any one or a combination of at least two of polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose, or chitosan, wherein typical but non-limiting combinations include combinations of polyvinyl alcohol and carboxymethyl cellulose or combinations of carboxymethyl cellulose and hydroxyethyl cellulose, etc.

[0026] Preferably, the mass percentage of the adhesive in the suspension is 0.5%-5%, for example, it can be 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0027] The present invention preferably controls the mass percentage content of the binder within a specific range, which can improve the compressive strength of the particles without clogging the atomizing disc.

[0028] Preferably, after mixing in step (1), the mixture is subjected to ultrasonication and dispersion in sequence to obtain a suspension.

[0029] Preferably, the temperature of the ultrasound is 30℃-50℃, for example, it can be 30℃, 32℃, 34℃, 36℃, 38℃, 40℃, 42℃, 44℃, 46℃, 48℃ or 50℃, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0030] Preferably, the frequency of the ultrasound is 30kHz-50kHz, for example, it can be 30kHz, 32kHz, 34kHz, 36kHz, 38kHz, 40kHz, 42kHz, 44kHz, 46kHz, 48kHz or 50kHz, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0031] Preferably, the ultrasound duration is 0.5h-1h, for example, it can be 0.5h, 0.6h, 0.8h or 1h, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0032] Preferably, the dispersion speed is 3000 r / min-4000 r / min, for example, it can be 3000 r / min, 3100 r / min, 3200 r / min, 3300 r / min, 3400 r / min, 3500 r / min, 3600 r / min, 3700 r / min, 3800 r / min, 3900 r / min or 4000 r / min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0033] Preferably, the dispersion time is 2h-4h, for example, it can be 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, 3.2h, 3.4h, 3.6h, 3.8h or 4h, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0034] Preferably, the temperature of the condensation treatment in step (2) is 0℃-5℃, for example, it can be 0℃, 1℃, 2℃, 3℃, 4℃ or 5℃, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0035] The present invention preferably controls the temperature of the condensation treatment within a specific range, which can reduce crystallization during the spraying process and is beneficial to increasing the specific surface area and pore size of inorganic functional materials.

[0036] Preferably, an alkaline solution is added before the condensation treatment.

[0037] Preferably, the alkaline solution includes ammonia.

[0038] Preferably, the mass of the alkaline solution is 0.1%-0.3% of the mass of the suspension, for example, it can be 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28% or 0.3%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0039] Preferably, the mass concentration of the ammonia water is 25%-28%, for example, it can be 25%, 26%, 27% or 28%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0040] Preferably, the gas used for spray drying in step (2) includes nitrogen.

[0041] The present invention preferably controls the drying gas to be nitrogen, which can make the particle size more uniform and the particle size distribution narrower.

[0042] Preferably, the gas flow rate is 300L / h-600L / h, for example, it can be 300L / h, 320L / h, 350L / h, 380L / h, 400L / h, 420L / h, 450L / h, 480L / h, 500L / h, 520L / h, 550L / h, 580L / h or 600L / h, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0043] Preferably, the inlet air temperature of the spray dryer is 180℃-220℃, for example, it can be 180℃, 185℃, 190℃, 195℃, 200℃, 205℃, 210℃, 215℃ or 220℃, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0044] Preferably, the outlet air temperature of the spray dryer is 80℃-110℃, for example, it can be 80℃, 85℃, 90℃, 95℃, 100℃, 105℃ or 110℃, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0045] The present invention preferably controls the inlet and outlet air temperatures of the spray dryer within a specific range, which allows the inorganic particles to lose water rapidly, maintain the spherical shape of the liquid particles, and prevents breakage due to uneven water loss.

[0046] Preferably, the spray drying pressure is 0.05MPa-0.2MPa, for example, it can be 0.05MPa, 0.06MPa, 0.07MPa, 0.08MPa, 0.1MPa, 0.12MPa, 0.14MPa, 0.16MPa, 0.18MPa or 0.2MPa, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable, with 0.2MPa being the preferred value.

[0047] Preferably, the feed rate of the spray dryer is 300 mL / h-4000 mL / h, for example, it can be 300 mL / h, 320 mL / h, 340 mL / h, 360 mL / h, 380 mL / h, 400 mL / h, 1000 mL / h, 2000 mL / h, 3000 mL / h or 4000 mL / h, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0048] The present invention preferably controls the feed rate of spray drying within a specific range, which can regulate the particle size of inorganic functional powder materials.

[0049] Preferably, the calcination temperature in step (2) is 400℃-1200℃, for example, it can be 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, 1000℃, 1100℃ or 1200℃, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0050] The present invention preferably controls the calcination temperature within a specific range, which can improve the crystallinity of the particles and increase the compressive strength of the inorganic functional powder material.

[0051] Preferably, the calcination includes any one of room temperature calcination, atmospheric pressure calcination, or microwave calcination, with microwave calcination being the preferred method.

[0052] The present invention preferably controls the calcination by microwave calcination, which can make the inorganic functional materials have higher compressive strength and more uniform pore size and particle size.

[0053] Preferably, the calcination time is 2h-6h, for example, it can be 2h, 2.2h, 2.5h, 2.8h, 3h, 3.2h, 3.5h, 3.8h, 4h, 4.2h, 4.5h, 4.8h, 5h, 5.2h, 5.5h, 5.8h or 6h, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0054] As a preferred embodiment of the first aspect of the present invention, the preparation method includes the following steps:

[0055] (1) Mix inorganic particles, dispersant, and binder, then sonicate at 30℃-50℃ and 30kHz-50kHz for 0.5h-1h, followed by dispersion at 3000r / min-4000r / min for 2h-4h to obtain a suspension; in the suspension, the mass percentage of dispersant is 0.1%-2.5%, the mass percentage of inorganic particles is 10%-50%, and the mass percentage of binder is 0.5%-5%. The dispersant includes any one or a combination of at least two of sodium polyacrylate, sodium polycarboxylate, sodium dodecylbenzenesulfonate, sodium citrate, sodium metaphosphate, or sodium pyrophosphate; the inorganic particles include any one or a combination of at least two of alumina, magnesium oxide, silicon oxide, zirconium oxide, aluminum silicate, basic calcium phosphate, or calcium fluorophosphate; the particle size of the inorganic particles is 1nm-20μm; the binder includes any one or a combination of at least two of polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose, or chitosan.

[0056] (2) Add 25%-28% ammonia water to the suspension obtained in step (1), wherein the mass of the ammonia water accounts for 0.1%-0.3% of the mass of the suspension. Then, perform condensation treatment at 0℃-5℃. After that, spray dry with nitrogen gas under the conditions of gas flow rate of 300L / h-600L / h, inlet air temperature of 180℃-220℃, outlet air temperature of 80℃-110℃, pressure of 0.05MPa-0.2MPa, and feed rate of 300mL / h-4000mL / h. Then, calcine at 400℃-1200℃ for 2h-6h to obtain the inorganic functional powder material.

[0057] Secondly, the present invention provides an inorganic functional powder material with a porous microsphere structure, wherein the inorganic functional powder material is obtained by the preparation method of the inorganic functional powder material with a porous microsphere structure described in the first aspect of the present invention; the inorganic functional powder material is spherical and / or ellipsoidal in shape; the inorganic functional powder material contains any one or a combination of at least two of cross-linked pores, through pores or blind pores.

[0058] In this invention, the inorganic functional powder material has a porous microsphere structure, with a spherical and / or ellipsoidal shape, and contains abundant internal voids, including any one or a combination of at least two of cross-linked pores, through pores, or blind pores. Therefore, the inorganic functional powder material provided by this invention has a large specific surface area and pore size, with uniform particle size and pore size distribution, adjustable size, and good compressive strength. It can be used in fields such as coating fillers, bone filler materials, protein separation media, and drug sustained-release carriers.

[0059] Preferably, the particle size of the inorganic functional powder material is 500nm-200μm, for example, it can be 500nm, 600nm, 800nm, 1μm, 20μm, 40μm, 50μm, 80μm, 100μm, 120μm, 180μm or 200μm, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0060] Preferably, the pore size of the inorganic functional powder material is 0nm-500nm, for example, it can be 0nm, 10nm, 20nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] (1) The method for preparing inorganic functional powder materials with porous microsphere structures provided by this invention can control the specific surface area and compressive strength of inorganic functional powder materials, achieving higher compressive strength while ensuring a larger specific surface area. Furthermore, the pore size and particle size can be controlled. Taking rod-shaped basic calcium phosphate with a particle size of 50 nm as an example, under optimal conditions, the resulting inorganic functional powder material has a compressive strength ≥ 7.4 MPa and a specific surface area ≥ 58.3 m². 2 / g, pore volume ≥0.47cm³ 3 / g, with an average pore size ≥35.6nm and a median particle size ≥17.5μm; taking needle-shaped basic calcium phosphate with a particle size of 100nm as an example, the resulting inorganic functional powder material has a compressive strength ≥10.6MPa and a specific surface area ≥80.2m². 2 / g, pore volume ≥0.49cm³ 3 / g, with an average pore size ≥46.4nm and a median particle size ≥11.2μm; taking columnar calcium fluorophosphate with a particle size of 140nm as an example, the compressive strength of the obtained inorganic functional powder material is ≥12.1MPa, and the specific surface area is ≥24.16m². 2 / g, pore volume ≥0.16cm³ 3 / g, average pore size ≥12.4nm, median particle size ≥94.2μm.

[0063] (2) The method for preparing inorganic functional powder materials with porous microsphere structure provided by the present invention is simple to operate and can be promoted industrially.

[0064] (3) The inorganic functional powder material with porous microsphere structure provided by the present invention has a large specific surface area, abundant pores, uniform particle size and pore size distribution, and high compressive strength. It can be used in the fields of coating filler, bone filling material, protein separation medium and drug sustained release carrier. Attached Figure Description

[0065] Figure 1 This is a scanning electron microscope image of the inorganic functional powder material with a porous microsphere structure described in Embodiment 1 of the present invention.

[0066] Figure 2 This is a partial scanning electron microscope image of the inorganic functional powder material with a porous microsphere structure described in Embodiment 1 of the present invention. Detailed Implementation

[0067] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.

[0068] Example 1

[0069] This embodiment provides a method for preparing inorganic functional powder materials with porous microsphere structures, the preparation method comprising the following steps:

[0070] (1) Mix 200 mL of water and sodium pyrophosphate, then add rod-shaped basic calcium phosphate with a particle size of 50 nm and polyvinyl alcohol of type 1799, sonicate at 40 °C and 40 kHz for 0.5 h, and then disperse at 3500 r / min for 4 h to obtain a suspension; the mass percentage of sodium pyrophosphate in the suspension is 1%, the mass percentage of basic calcium phosphate is 30%, and the mass percentage of polyvinyl alcohol is 1%;

[0071] (2) Add 26% ammonia water to the suspension obtained in step (1), wherein the mass of the ammonia water accounts for 0.2% of the mass of the suspension. Then, perform condensation treatment at 2°C. After that, under the conditions of gas flow rate of 420L / h, inlet air temperature of 195°C, outlet air temperature of 100°C, pressure of 0.1MPa, and feed rate of 500mL / h, nitrogen gas is introduced for spray drying. Then, microwave calcination is performed at 600°C for 4h to obtain the inorganic functional powder material.

[0072] This embodiment also provides an inorganic functional powder material with a porous microsphere structure, which is obtained by the above-described preparation method, such as... Figure 1-2 As shown, the inorganic functional powder material is spherical and has abundant pores on its surface, including cross-linked pores, through pores and blind pores. The particle size is 4-40 μm, the median particle size is 17.5 μm, and the average pore size is 35.6 nm.

[0073] Example 2

[0074] This embodiment provides a method for preparing inorganic functional powder materials with porous microsphere structures, the preparation method comprising the following steps:

[0075] (1) Mix 200 mL of water and sodium pyrophosphate, then add needle-shaped basic calcium phosphate with a particle size of 100 nm and chitosan, sonicate at 30 °C and 50 kHz for 0.6 h, and then disperse at 3000 r / min for 3 h to obtain a suspension; the mass percentage of sodium pyrophosphate in the suspension is 0.5%, the mass percentage of basic calcium phosphate is 50%, and the mass percentage of chitosan is 5%;

[0076] (2) Add 25% ammonia water to the suspension obtained in step (1), wherein the mass of the ammonia water accounts for 0.1% of the mass of the suspension. Then, perform condensation treatment at 0°C. After that, under the conditions of gas flow rate of 300L / h, inlet air temperature of 220°C, outlet air temperature of 80°C, pressure of 0.2MPa, and feed rate of 300mL / h, nitrogen gas is introduced for spray drying. Then, microwave calcination is performed at 400°C for 6h to obtain the inorganic functional powder material.

[0077] Example 3

[0078] This embodiment provides a method for preparing inorganic functional powder materials with porous microsphere structures, the preparation method comprising the following steps:

[0079] (1) Mix 200 mL of water and sodium dodecylbenzenesulfonate, then add columnar calcium fluorophosphate with a particle size of 140 nm and carboxymethyl cellulose, sonicate at 30 kHz for 1 h at 50 °C, and then disperse at 4000 r / min for 2 h to obtain a suspension; the mass percentage of sodium dodecylbenzenesulfonate in the suspension is 2.5%, the mass percentage of calcium fluorophosphate is 10%, and the mass percentage of chitosan is 0.5%;

[0080] (2) Add 28% ammonia water to the suspension obtained in step (1), wherein the mass of the ammonia water accounts for 0.3% of the mass of the suspension. Then, perform condensation treatment at 5°C. After that, under the conditions of gas flow rate of 600L / h, inlet air temperature of 180°C, outlet air temperature of 110°C, pressure of 0.05MPa, and feed rate of 4000mL / h, nitrogen gas is introduced for spray drying. Then, microwave calcination is performed at 1200°C for 2h to obtain the inorganic functional powder material.

[0081] Example 4

[0082] This embodiment provides a method for preparing inorganic functional powder materials with porous microsphere structure, which differs from Example 1 only in that the calcination temperature is 300℃.

[0083] Example 5

[0084] This embodiment provides a method for preparing inorganic functional powder materials with porous microsphere structure. The only difference from Example 1 is that the calcination temperature is 1300℃.

[0085] Example 6

[0086] This embodiment provides a method for preparing an inorganic functional powder material with a porous microsphere structure. The only difference from Example 1 is that the mass percentage content of polyvinyl alcohol is 0.05%.

[0087] Example 7

[0088] This embodiment provides a method for preparing an inorganic functional powder material with a porous microsphere structure. The only difference from Example 1 is that the mass percentage of polyvinyl alcohol is 6%.

[0089] Comparative Example 1

[0090] This comparative example provides a method for preparing inorganic functional powder materials, which differs from Example 1 only in that polyvinyl alcohol is not added.

[0091] Comparative Example 2

[0092] This comparative example provides a method for preparing inorganic functional powder materials. The only difference from Example 1 is that after the suspension is condensed, it is centrifuged, and the solid product obtained by centrifugation is vacuum dried at 60°C for 10 hours and then microwave calcined at 600°C for 4 hours to obtain inorganic functional powder materials.

[0093] The BET specific surface area, pore volume, and average pore size of the inorganic functional powder materials prepared in Examples 1-7 and Comparative Examples 1-2 were tested using an ASAP 2020Plus 2.00 instrument manufactured by Micromeritics. The results are shown in Table 1.

[0094] The median particle size of the inorganic functional powder materials prepared in Examples 1-7 and Comparative Examples 1-2 was determined using a laser particle size analyzer, model Mastersizer 2020, manufactured by Malvern. The results are shown in Table 1.

[0095] Table 1

[0096]

[0097] The following points can be observed from Table 1:

[0098] (1) As can be seen from Examples 1-6, using the method for preparing inorganic functional powder materials with porous microsphere structure provided by the present invention, taking rod-shaped basic calcium phosphate with a particle size of 50 nm as an example, under preferred conditions, the compressive strength of the obtained inorganic functional powder material is ≥7.4 MPa, and the specific surface area is ≥58.3 m². 2 / g, pore volume ≥0.47cm³ 3 / g, with an average pore size ≥35.6nm and a median particle size ≥17.5μm; taking needle-shaped basic calcium phosphate with a particle size of 100nm as an example, the resulting inorganic functional powder material has a compressive strength ≥10.6MPa and a specific surface area ≥80.2m². 2 / g, pore volume ≥0.49cm³ 3 / g, with an average pore size ≥46.4nm and a median particle size ≥11.2μm; taking columnar calcium fluorophosphate with a particle size of 140nm as an example, the compressive strength of the obtained inorganic functional powder material is ≥12.1MPa, and the specific surface area is ≥24.16m². 2 / g, pore volume ≥0.16cm³ 3 / g, average pore size ≥12.4nm, median particle size ≥94.2μm.

[0099] (2) A comprehensive comparison of the data from Examples 1 and 4-5 shows that the calcination temperature in Example 1 is 600℃, which is higher than the calcination temperatures of 300℃ and 1300℃ in Examples 4 and 5, respectively. Since the specific surface area and pore size are linked, the compressive strength of the inorganic functional powder material in Example 1 is higher than that in Example 4, and the specific surface area of ​​the inorganic functional powder material in Example 1 is higher than that in Example 5. This indicates that the present invention preferably controls the calcination temperature, which can improve the specific surface area of ​​the inorganic functional powder material while ensuring high compressive strength.

[0100] (3) A comprehensive comparison of the data from Examples 1, 6-7 and Comparative Example 1 shows that the polyvinyl alcohol content in Example 1 is 1%, which is 0.05%, 6% and 0% in Examples 6, 7 and Comparative Example 1, respectively. The inorganic functional powder material obtained in Comparative Example 1 has no pores, while pores are present in Examples 1 and 6-7. Furthermore, the compressive strength of the inorganic functional powder material in Example 1 is higher than that in Example 6, and the specific surface area of ​​the inorganic functional powder material in Example 1 is higher than that in Example 7. This indicates that the present invention can obtain an inorganic functional powder material with a porous structure by adding a binder. Moreover, the present invention preferably controls the mass percentage of the binder, which can improve the specific surface area of ​​the inorganic functional powder material while ensuring high compressive strength.

[0101] (4) By comparing the data of Example 1 and Comparative Example 2, it can be seen that the only difference between Comparative Example 2 and Example 1 is that after the suspension is condensed, it is centrifuged, and the solid product obtained by centrifugation is vacuum dried at 60°C for 10 hours and then microwave calcined at 600°C for 4 hours to obtain inorganic functional powder material. The inorganic functional powder material obtained in Comparative Example 2 has no pores, while the one in Example 1 has pores. This shows that the present invention can prepare inorganic functional powder material with porous structure by spray drying.

[0102] In summary, the method for preparing inorganic functional powder materials with porous microsphere structures provided by this invention can control the specific surface area and compressive strength of the material. Taking rod-shaped basic calcium phosphate with a particle size of 50 nm as an example, under optimal conditions, the compressive strength of the obtained inorganic functional powder material is ≥7.4 MPa, and the specific surface area is ≥58.3 m².2 / g, pore volume ≥0.47cm³ 3 / g, with an average pore size ≥35.6nm and a median particle size ≥17.5μm; taking needle-shaped basic calcium phosphate with a particle size of 100nm as an example, the resulting inorganic functional powder material has a compressive strength ≥10.6MPa and a specific surface area ≥80.2m². 2 / g, pore volume ≥0.49cm³ 3 / g, with an average pore size ≥46.4nm and a median particle size ≥11.2μm; taking columnar calcium fluorophosphate with a particle size of 140nm as an example, the compressive strength of the obtained inorganic functional powder material is ≥12.1MPa, and the specific surface area is ≥24.16m². 2 / g, pore volume ≥0.16cm³ 3 / g, with an average pore size ≥12.4nm and a median particle size ≥94.2μm, the resulting inorganic functional powder material has a large specific surface area, abundant pores, uniform particle size and pore size distribution, and high compressive strength.

[0103] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing an inorganic functional powder material with a porous microsphere structure, characterized in that, The preparation method includes the following steps: (1) Mix inorganic particles, dispersant and binder to obtain a suspension; (2) The suspension obtained in step (1) is subjected to condensation treatment, and then spray drying and calcination are performed in sequence to obtain the inorganic functional powder material; In the suspension, the dispersant has a mass percentage content of 0.1%-2.5%, and the binder has a mass percentage content of 0.5%-5%. The calcination temperature in step (2) is 400℃-700℃; The condensation treatment in step (2) is performed at a temperature of 0℃-4℃; The inorganic particles are basic calcium phosphate or calcium fluorophosphate.

2. The preparation method according to claim 1, characterized in that, In step (1), the dispersant is first mixed with the solvent, and then mixed with the inorganic particles and the binder.

3. The preparation method according to claim 1, characterized in that, The dispersant includes any one or a combination of at least two of sodium polyacrylate, sodium polycarboxylate, sodium dodecylbenzenesulfonate, sodium citrate, sodium metaphosphate, or sodium pyrophosphate.

4. The preparation method according to claim 1, characterized in that, The inorganic particles include inorganic metal oxides and / or inorganic salts.

5. The preparation method according to claim 1, characterized in that, The inorganic particles in the suspension comprise 10%-50% by mass.

6. The preparation method according to claim 1, characterized in that, The inorganic particles have a particle size of 1 nm to 20 μm.

7. The preparation method according to claim 6, characterized in that, The inorganic particles have a particle size of 40nm-500nm.

8. The preparation method according to claim 1, characterized in that, The inorganic particles have the morphology of any one or a combination of at least two of the following: rod-shaped, needle-shaped, plate-shaped, spherical, ellipsoidal, columnar, or plate-shaped.

9. The preparation method according to claim 1, characterized in that, The adhesive includes any one or a combination of at least two of polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose, or chitosan.

10. The preparation method according to claim 1, characterized in that, After mixing in step (1), the mixture is subjected to ultrasonication and dispersion in sequence to obtain a suspension.

11. The preparation method according to claim 10, characterized in that, The temperature of the ultrasound is 30℃-50℃.

12. The preparation method according to claim 10, characterized in that, The frequency of the ultrasound is 30kHz-50kHz.

13. The preparation method according to claim 10, characterized in that, The ultrasound duration is 0.5h-1h.

14. The preparation method according to claim 10, characterized in that, The dispersion speed is 3000 r / min-4000 r / min.

15. The preparation method according to claim 10, characterized in that, The dispersion time is 2h-4h.

16. The preparation method according to claim 1, characterized in that, An alkaline solution is added before the condensation treatment.

17. The preparation method according to claim 16, characterized in that, The alkaline solution includes ammonia.

18. The preparation method according to claim 16, characterized in that, The mass of the alkaline solution is 0.1%-0.3% of the mass of the suspension.

19. The preparation method according to claim 17, characterized in that, The mass concentration of the ammonia water is 25%-28%.

20. The preparation method according to claim 1, characterized in that, The gas used for spray drying in step (2) includes nitrogen.

21. The preparation method according to claim 20, characterized in that, The flow rate of the gas is 300L / h-600L / h.

22. The preparation method according to claim 1, characterized in that, The inlet air temperature for the spray dryer is 180℃-220℃.

23. The preparation method according to claim 1, characterized in that, The outlet air temperature of the spray dryer is 80℃-110℃.

24. The preparation method according to claim 1, characterized in that, The spray drying pressure is 0.05MPa-0.2MPa.

25. The preparation method according to claim 1, characterized in that, The calcination time is 2h-6h.

26. The preparation method according to claim 1, characterized in that, The preparation method includes the following steps: (1) Mix inorganic particles, dispersant and binder, then sonicate at 30℃-50℃ and 30kHz-50kHz for 0.5h-1h, then disperse at 3000r / min-4000r / min for 2h-4h to obtain a suspension; in the suspension, the mass percentage of dispersant is 0.1%-2.5%, the mass percentage of inorganic particles is 10%-50%, and the mass percentage of binder is 0.5%-5%. The dispersant includes any one or a combination of at least two of sodium polyacrylate, sodium polycarboxylate, sodium dodecylbenzenesulfonate, sodium citrate, sodium metaphosphate or sodium pyrophosphate; the inorganic particles are basic calcium phosphate or calcium fluorophosphate; the particle size of the inorganic particles is 1nm-20μm; the binder includes any one or a combination of at least two of polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose or chitosan. (2) Add 25%-28% ammonia water to the suspension obtained in step (1), wherein the mass of the ammonia water accounts for 0.1%-0.3% of the mass of the suspension. Then, perform condensation treatment at 0℃-4℃. After that, spray dry the suspension with nitrogen at a flow rate of 300L / h-600L / h, an inlet air temperature of 180℃-220℃, an outlet air temperature of 80℃-110℃, a pressure of 0.05MPa-0.2MPa, and a feed rate of 300mL / h-4000mL / h. Then, calcine the suspension at 400℃-700℃ for 2h-6h to obtain the inorganic functional powder material.

27. An inorganic functional powder material with a porous microsphere structure, characterized in that, The inorganic functional powder material is obtained by the preparation method of inorganic functional powder material with porous microsphere structure as described in any one of claims 1-26; The inorganic functional powder material is spherical and / or ellipsoidal in shape; The inorganic functional powder material contains any one or a combination of at least two of the following: cross-linked pores, through pores, or blind pores.

28. The inorganic functional powder material according to claim 27, characterized in that, The particle size of the inorganic functional powder material is 500nm-200μm.

29. The inorganic functional powder material according to claim 27, characterized in that, The pore size of the inorganic functional powder material is 0nm-500nm.

Citation Information

Patent Citations

  • Porous spherical calcium phosphate filling material and preparing method thereof

    CN104548213A

  • Porous calcium phosphate microsphere material with surface big holes and preparation method and application of porous calcium phosphate microsphere material

    CN105056298A

  • Preparation method of structure size-controllable hydroxyapatite powder for plasma thermal spraying

    CN103723699A

  • Hydroxyapatite microspheres for injecting filling preparation and preparation method thereof

    CN112875665A

  • Method for producing silica particle

    JP2016190769A